2012
DOI: 10.1159/000341273
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Blood Pressure Stability with Hypertonic Mannitol during Hemodialysis Initiation

Abstract: Background: Intradialytic hypotensive events are common among hemodialysis patients and are associated with a variety of patient- and procedure-related factors, including intradialytic decline in plasma osmolality. Prior studies and practice have suggested that administration of osmotically active drugs may ameliorate blood pressure decline during chronic hemodialysis. Methods: Clinical and treatment data were collected for 102 consecutive patients requiring initiation of renal replacement therapy in 2 major t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Prior reports of increased thirst and inter-dialytic weight gain (IDWG) tempered the initial enthusiasm of these findings [12,34], but more recently the use of biofeedback-controlled sodium profiling appears to have less associated IDWG [35]. Other methods include the administration of hypertonic mannitol and other hypertonic solutions [15,30,36,37]. In addition to trans-cellular fluid shifts due to osmotic changes, rapid decline of intra-vascular osmolality may suppress the release of vasopressin, which has pressor-like effects on the vasculature; in support of this concept, infusion of vasopressin during hemodialysis has been associated with improved hemodynamic stability [38].…”
Section: Discussionmentioning
confidence: 99%
“…Prior reports of increased thirst and inter-dialytic weight gain (IDWG) tempered the initial enthusiasm of these findings [12,34], but more recently the use of biofeedback-controlled sodium profiling appears to have less associated IDWG [35]. Other methods include the administration of hypertonic mannitol and other hypertonic solutions [15,30,36,37]. In addition to trans-cellular fluid shifts due to osmotic changes, rapid decline of intra-vascular osmolality may suppress the release of vasopressin, which has pressor-like effects on the vasculature; in support of this concept, infusion of vasopressin during hemodialysis has been associated with improved hemodynamic stability [38].…”
Section: Discussionmentioning
confidence: 99%
“…Our group examined 102 patients initiating hemodialysis at two major academic teaching hospitals (one of which routinely administered mannitol; the other did not) in an observational cohort study. We noted that the administration of hypertonic mannitol was associated with a 5 mm Hg higher nadir SBP during HD and a lower adjusted odds of experiencing hypotension (OR 0.50; 95% CI 0.29‐0.83) . Caveats of this study included the small sample, observational nature of the study and the potential for a center effect; strengths include the reduced likelihood of confounding by indication, as the use of mannitol vs not was based on protocol, as opposed to individual prescribing practices.…”
Section: Interventions To Minimize Intra‐dialytic Osmolality Declinementioning
confidence: 95%
“…Another technique to minimize reductions in IDH during intermittent HD is the intradialytic administration of hypertonic mannitol, a six‐carbon sugar that can temporarily increase plasma osmolarity during hemodialysis. In a retrospective study of hemodialysis initiations for both AKI and end‐stage renal disease at two separate institutions, one of which routinely used intradialytic mannitol, McCausland et al found fewer IDH events in patients receiving mannitol Supporting systemic pressures: midodrine has been found to be effective in increasing nadir systolic and diastolic blood pressures in a systematic review of studies involving patients on maintenance hemodialysis .…”
Section: Prevention/treatmentmentioning
confidence: 99%